CORRUPTION IN UKRAINE AS LEGACY OF THE SOVIET STATE ADMINISTRATION - Сопілко, Ірина Миколаївна; Армаш, Надія Олексіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article presents the genesis of the formation of corruption systems in the Soviet era. The preconditions for the existence of corruption and their impact on modern relations in public administration are analyzed. Research methods: the use of the historical method of cognition allowed to concentrate the accumulated scientific knowledge and practice of applying anti-corruption legislation. Results: the prerequisites of a low level of effectiveness in preventing corruption are identified, ways of overcoming such prerequisites in modern society are indicated. Discussion of the problem: the eradication of corruption as a phenomenon, taking into account the historical experience of anti-corruption activities.